Self acceptance of students repeating classes in Ibadan metropolis: relationship with parents’ sense- of- competence, locus of control and quality of parents-child-relationship (2017)
Self acceptance has been documented to be one of the non-intellectual factors in the students’ personalities that reinforce and foster academic success or failure. Descriptive survey design was adopted to examine the relationship between parent sense-of- competence, locus of control, parent-child relationship and self-acceptance among secondary school students in Ibadan Metropolis. Simple random sampling technique was utilized to select nine public schools from Ibadan metropolis out of which 450 senior secondary school repeaters were purposively drawn. The students filled three self-report measures while their parents completed parents’ sense-of-competence scale. Results indicate that there was positive relationship between parents’ sense- of -competence (r=.220; p< 0.01); locus of control (r=.193; p<0.01); quality of parent-child relationship (r=.185; p<0.01) and students’ self-acceptance. The independent variables jointly contributed 8% variance to the prediction of the students’ self-acceptance. Parent sense of competence was most potent on predicting self acceptance (Beta=.175; t=3.769; P< 0.01). It concluded that the hypothesized variables have weak positive relationship with students’ self-acceptance. It recommends that Counselling Psychologist should organize parent education programme to improve parents parenting practices, competencies, and skill for effective parent-teen-communication